Development of the Dutch Chaplaincy Outcome Measure - Anja Visser; Annelieke Damen; Carmen Schuhmann; X. J. S. (Sujin) Rosie; Hanneke Muthert; Erik Olsman; Marjo van Zundert; Gaby Jacobs (Religions)
Outcome research is becoming increasingly important in chaplaincy. However, current outcome measures rarely reflect outcomes reflecting chaplaincy goals. This limits the understanding of the effect of chaplaincy care. Therefore, we have developed the Dutch Chaplaincy Outcome Measure (NUGV). It uses a Q-methodology, comprising a two-step sorting task of 25 statements and a brief post-sorting interview. The statements relate to four goals of chaplaincy: worldview development, coping with life events and circumstances, relational affirmation, and transcendence and connectedness. The statements were derived from a literature review, interviews with 24 clients of chaplaincy in primary, outpatient, or community care, and eight focus groups with clients, chaplaincy, and other professionals in primary, outpatient, or community care. Acceptability, clarity, and (face) validity were examined with a client council, in a workshop, and through two pilot studies. They were found to be satisfactory. Thus, the NUGV seems to be a promising instrument for outcome assessment in chaplaincy. More research is needed on the construct validity and specificity of the outcomes, as well as the use of the instrument in inpatient settings and among people with lower language and cognitive capabilities. We recommend that researchers administer the NUGV in person, to enable more support during the sorting task and to facilitate richer data in the post-sorting interview.